Application of Robotic Manipulators in Mechanical Engineering: Prospects and Problems. - Qosimova Zamira Medatovna; Uraimov Muhammaddiyor Bakhodir ugli (Genius Journals, 2023)
The article discusses the use of robotic manipulators in mechanical engineering. The prospects of using robotic manipulators for automation of production processes, as well as problems associated with their implementation, are discussed
Keywords: robots; manipulators; mechanical engineering; cost